A Comparison of Lipopolysaccharide-Binding Protein With C-Reactive Protein as Early Inflammation Markers in Pediatric Oncology Patients. Issue 5 (September 2015) - Sklavou, Rigina; Karavanaki, Kyriaki; Kossiva, Lydia; Critselis, Eleni; Gourgiotis, Dimitris; Tsolia, Maria; Giannaki, Maria; Marmarinos, Antonis; Konstantinou, Maria; Sdogou, Triantafyllia; Polychronopoulou, Sophia
Abstract : Background: Cancer patients have a variable risk of bacterial infection, associated with high mortality. Lipopolysaccharide-binding protein (LBP) has been suggested as a possible predictor of gram-negative bacteremia. We aimed to compare LBP with C-reactive protein (CRP) as early markers of bacterial infection in febrile pediatric cancer patients. Methods: We prospectively studied 37 (mean ± SD age, 6.7 ± 5.1 years) cancer patients presenting with 51 febrile episodes and 20 cancer patients without an infection (controls). At fever onset and after 48 hours, white blood cell count, LBP, and CRP were measured and cultures were obtained. Results: On admission and in 48 hours both LBP (47.5 vs. 29.6 ng/mL, P = 0.0004) and CRP (33.1 vs. 11.0 mg/L, P = 0.005) were higher in the group with bacterial infection. Nevertheless, neither LBP nor CRP on admission could discriminate patients with a positive culture and those with gram-negative bacteremia. However, LBP levels in 48 hours were higher in patients with a positive culture. When comparing LBP and CRP on admission in distinguishing bacterial from viral infections, LBP had a better sensitivity, but a lower specificity than CRP. Moreover, both LBP and CRP had high positive predictive values (93.3%, 94.7%) and low negative predictive values (52.2%, 62.5%), respectively. Conclusions: Both LBP and CRP at presentation and in 48 hours could differentiate bacterial from viral infections in febrile cancer patients. However, LBP is not a better marker than CRP as neither one on admission could discriminate positive from negative cultures and detect gram-negative bacteremia, whereas both markers have low negative predictive values. Thus, serial measurements are necessary for the detection and follow-up of a bacterial infection in pediatric cancer patients.